Evaluation of the antibacterial activity of human cathelicidin peptide-LL-37 in the presence of acidified nitrite - Hanna Aka, Safaa Toma (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Bacterial resistance to conventional antibacterial agents has increased recently and this resistance results in complicated infections. Multiple protective mechanisms can evolve in mammalians to maintain the body protected from infections. Human cathelicidin antimicrobial peptide LL-37 and acidified nitrite are important components of the innate immune system that partake in preventing infections. Cathelicidin peptide LL-37 can be produced by epithelial tissues as well as by macrophages after microbial infections. This study was carried out to evaluate the antibacterial activity of LL-37 and acidified nitrite (AN) both individually and combined for their effect against the standard the strains of E.coli ATCC 25922 and S. aureus ATCC 25923. Methods: Flat-bottom micro well plates (96 wells) were used for the determination of bacteriostatic activity. Sodium nitrite (NaNO2) and ascorbic acid (AA) were used to produce acidified nitrite (AN). The singular and combined forms of the antibacterial agents were used for evaluating the antibacterial activities of LL-37 through estimation optical density values at 480nm (OD480nm). Results: The LL-37 peptide showed antibacterial activity against E.coli ATCC 25922 and S. aureus ATCC 25923. The antibacterial efficacy was enhanced when the peptide was tested in combination with AN (P <0.001). In contrast, the combination of LL-37 with NaNO2 and AA has an antagonistic effect (P <0.001) on its antimicrobial properties. Conclusion: The combination of LL-37 with AN has a synergistic on the peptide’s antimicrobial effect. Therefore, LL-37 which might show little antibacterial activity when used alone can provide protection when used in combination therapy with other antimicrobial agents.